The - Christensen, Clayton M. (Harvard Business Review Press, 2016)
No business can afford to ignore the theory of disruptive innovation. But the nuances of Clayton Christensen’s foundational thinking on the subject are often forgotten or misinterpreted. To achieve continuing growth in your business while defending against upstarts, you need to understand clearly what disruption is and how it works, and know how it applies to your industry and your company. In this collection of Christensen’s most influential articles―carefully selected by Harvard Business Review’s editors―his incisive arguments, clear theories, and readable stories give you the tools you need to understand disruption and what to do about it. The collection features Christensen’s newest article looking back on 20 years of disruptive innovation: what it is, and what it isn’t